Better than before ebook What i learned about making and breaking habits--to sleep more, quit sugar, procrastinate less, and generally build a happier life. - Rubin, Gretchen (2015)
NEW YORK TIMES  BESTSELLER • The author of  The Happiness Project  and “a force for real change” (Brené Brown) examines how changing our habits can change our lives.   “If anyone can help us stop procrastinating, start exercising, or get organized, it’s Gretchen Rubin. The happiness guru takes a sledgehammer to old-fashioned notions about change.”— Parade   Most of us have a habit we’d like to change, and there’s no shortage of expert advice. But as we all know from tough experience, no magic, one-size-fits-all solution exists. It takes work to make a habit, but once that habit is set, we can harness the energy of habits to build happier, stronger, more productive lives.   In  Better Than Before,  acclaimed writer Gretchen Rubin identifies every approach that actually works. She presents a practical, concrete framework to allow readers to understand their habits—and to change them for good.    Infused with Rubin’s compelling voice, rigorous research, and easy humor, and packed with vivid stories of lives transformed,  Better Than Before  explains the (sometimes counterintuitive) core principles of habit formation and answers the most perplexing questions about habits:    • Why do we find it tough to create a habit for something we love to do?  • How can we keep our healthy habits when we’re surrounded by temptations?  • How can we help someone else change a habit?    Rubin reveals the true secret to habit change: first, we must know ourselves. When we shape our habits to suit ourselves, we can find success—even if we’ve failed before.    Whether you want to eat more healthfully, stop checking devices, or finish a project, the invaluable ideas in  Better Than Before  will start you working on your own habits—even before you’ve finished the book.